2017
DOI: 10.1177/0009922817743571
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of Child Maltreatment in Electronic Health Records

Abstract: International Classification of Diseases codes for child maltreatment can aid surveillance and research, but the extent to which they are used is not well established. We documented prevalence of the use of maltreatment-related codes, examined demographic characteristics of youth assigned these codes, and compared results with previous studies. Data were extracted from electronic health records of 0- to 21-year-olds assigned 1 of 15 maltreatment-related International Classification of Diseases, Ninth Revision,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 51 publications
2
27
1
Order By: Relevance
“…The limited documentation of codes in the medical record explicitly indicating maltreatment (n = 265) is consistent with results from prior studies in the literature. 24,25 Similar to those studies, we also found that including ICD-9-CM codes suggestive of maltreatment in this analysis increased detection of visits involving potential maltreatment by more than 12-fold. Susceptibility to maltreatment decreases with age, 4 placing younger children at the greatest risk for abuse and neglect.…”
Section: Discussionsupporting
confidence: 87%
“…The limited documentation of codes in the medical record explicitly indicating maltreatment (n = 265) is consistent with results from prior studies in the literature. 24,25 Similar to those studies, we also found that including ICD-9-CM codes suggestive of maltreatment in this analysis increased detection of visits involving potential maltreatment by more than 12-fold. Susceptibility to maltreatment decreases with age, 4 placing younger children at the greatest risk for abuse and neglect.…”
Section: Discussionsupporting
confidence: 87%
“…Few pediatric clinicians ask about ACEs or document childhood adversity in the medical record. 44 Notably, ACEs surveys do not typically include housing status, so even if ACEs surveillance became a routine part of pediatric or community healthcare, housing experiences and/or needs might not be considered without additional screening. While some clinical systems have piloted methods to screen for social determinants of health, including housing and ACEs, efforts are widely variable and lack consistent protocols across the field.…”
Section: Discussionmentioning
confidence: 99%
“…Few pediatric clinicians ask about ACEs or document childhood adversity in the medical record. 41 Notably, ACEs surveys do not typically include housing status, so even if ACEs surveillance became a routine part of pediatric or community healthcare, housing experiences and/or needs might not be considered without additional screening. While some clinical systems have piloted methods to screen for social determinants of health, including housing and ACEs, efforts are widely variable and lack consistent protocols across the field.…”
Section: Discussionmentioning
confidence: 99%